Effects of medicated enema and nasal drops using Triphaladi oil in the management of obesity - A pilot study - Sarvesh Kumar Singh; Preeti Swami; Kshipra Rajoria (Journal of Ayurveda and Integrative Medicine, 2020)
An open label, randomized, comparative, interventional pilot study was done to assess the effect of Lekhana Basti (medicated enema) and Rechana Nasya Karma (Errhine therapy) in the management of Sthoulya with special reference to obesity. In the study 30 clinically diagnosed patient of either sex were randomly divided into two groups. In Basti group, Lekhana Basti in Karma Basti manner was given for 30 days. Anuvasana Basti (enema with Triphaladi Taila) in the dose of 120 mL and Asthapana Basti (enema with Triphaladi decoction etc.) in the dose of approximately 960 mL was given. In Nasya group, Rechana nasya on alternate days was given with Triphaladi (oil) in the dose of 0.5 mL per nostril for total 28 days. The patients were assessed on objective criteria such as such as weight, chest circumference, mid-arm circumference, mid-thigh circumference, triceps skin fold thickness, sub-scapular skin fold thickness, abdominal skin fold thickness, waist-hip ratio and lipid profile. It was observed that Basti group was a better intervention in providing relief, however there intergroup standard deviation was low on most of the variable expect the lipid profile. The results suggest that the Nasya Karma may be developed as a better practical approach in obesity management.